2022
DOI: 10.1002/cncy.22623
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study: Comparison of TRPS1 and GATA3 immunoperoxidase staining using cytologic smears in entities reportedly positive for GATA3

Abstract: BACKGROUND: Metastatic breast carcinoma (mBC) is frequently encountered and may be challenging to diagnose as the tumor cells can morphologically resemble carcinomas of other primary origins. An additional challenge is that direct smears are often the only sample type available for immunostaining studies in cytology. Trichorhinophalangeal syndrome GATAbinding type 1 1 (TRPS1) is a highly sensitive marker for BC compared to the commonly used marker GATA3, especially in triple-negative BC (TNBC), in histologic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 43 publications
4
17
1
Order By: Relevance
“…Analogous results were also reported using whole tissue sections 20 . Recently, Rohra et al demonstrated TRPS1 as a valuable marker for metastatic breast carcinoma in direct cytology smears, with good sensitivity for both GATA3‐negative and GATA3‐positive breast carcinomas 21 . Wang et al also reported that TRPS1 was positive in 94.4% ( n = 36) of GATA3‐positive and 50% ( n = 2) GATA3‐negative metastatic breast carcinoma in pleural effusion specimens 22 .…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Analogous results were also reported using whole tissue sections 20 . Recently, Rohra et al demonstrated TRPS1 as a valuable marker for metastatic breast carcinoma in direct cytology smears, with good sensitivity for both GATA3‐negative and GATA3‐positive breast carcinomas 21 . Wang et al also reported that TRPS1 was positive in 94.4% ( n = 36) of GATA3‐positive and 50% ( n = 2) GATA3‐negative metastatic breast carcinoma in pleural effusion specimens 22 .…”
Section: Discussionsupporting
confidence: 53%
“…8 Therefore, the status of GATA3 expression in mesothelial cells or mesotheliomas remains controversial. In our breast and salivary duct carcinomas, 14,21 other carcinomas seldom express TRPS1, and those that do are mostly from the lung and gynecologic tract. 14,20 In the current study, TRPS1 expression was significantly lower than in other malignancies.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations